Food Irradiation for Food Safety: Consumer Awareness, Attitudes, and Acceptance Toward Irradiated Food in Indonesia - Fauzan, Ilham; Bukhari, Ahmad; Sumantri, Ari Tresna (Journal of Applied Food Technology, 2025)
Indonesia faces major food safety issues. Foodborne illness and food loss and waste (FLW) are affecting public health and the economy. This will likely continue unless these problems are addressed. Food irradiation is a non-thermal food processing technology that offers a promising means to address this issue by enhancing food safety and quality. However, the application of food irradiation could be limited. Consumer concerns could prevent the use of food irradiation in Indonesia due to limited knowledge and misconceptions regarding irradiation. This study examines Indonesian consumers’ awareness, attitudes, and acceptance toward irradiated food. Moreover, explores differences in acceptance across socio-demographic groups. An online survey was conducted from May to July 2025. A total of 386 respondents participated. Descriptive statistics were utilized to analyze awareness, attitudes, and acceptance, while comparative tests assessed socio-demographic differences. Results reveal surprisingly high acceptance: 69.2% are willing to buy, and 69.0% are willing to consume irradiated foods, despite generally low awareness (45.3%). Consumers reported moderate perceived risk, substantial perceived benefits, and high trust. Acceptance did not differ significantly by gender but was notably lower among older, higher-educated, and higher-income groups. Indicate Consumers with higher education and income appear to be more critical and selective than those with lower education and income. Communication efforts should focus on raising awareness and providing information to help consumers understand the advantages of food irradiation. Overall, this study provides valuable empirical evidence for policymakers, the food industry, and academics to support the safe and broad application of food irradiation.